Action mechanism of naphthofuranquinones against fluconazole-resistant Candida tropicalis strains evidenced by proteomic analysis: The role of increased endogenous ROS. (April 2018) - de Andrade Neto, João Batista; da Silva, Cecília Rocha; Campos, Rosana de Sousa; do Nascimento, Francisca Bruna Stefany Aires; Sampaio, Letícia Serpa; da Silva, Anderson Ramos; Josino, Maria Aparecida Alexandre; de Moraes, Manoel Odorico; Lobo, Marina Duarte Pinto; Moreno, Frederico Bruno Mendes Batista; Moreira, Ana Cristina de Oliveira Monteiro; de Azevedo Moreira, Renato; et al.
Abstract: The increased incidence of candidemia in terciary hospitals worldwide and the cross-resistance frequency require the new therapeutic strategies development. Recently, our research group demonstrated three semi-synthetic naphthofuranquinones (NFQs) with a significant antifungal activity in a fluconazole-resistant (FLC) C. tropicalis strain. The current study aimed to investigate the action's preliminary mechanisms of NFQs by several standardized methods such as proteomic and flow cytometry analyzes, comet assay, immunohistochemistry and confocal microscopy evaluation. Our data showed C. tropicalis 24 h treated with all NFQs induced an expression's increase of proteins involved in the metabolic response to stress, energy metabolism, glycolysis, nucleosome assembly and translation process. Some aspects of proteomic analysis are in consonance with our flow cytometry analysis which indicated an augmentation of intracellular ROS, mitochondrial dysfunction and DNA strand breaks (neutral comet assay and γ-H2AX detection). In conclusion, our data highlights the great contribution of ROS as a key event, probably not the one, associated to anti-candida properties of studied NFQs. Highlights: Proteomic analysis of Candida tropicalis strains exposed to Naphthofuranquinones. Naphthofuranquinones induced an increase in the total intracellular levels of ROS. Naphthofuranquinones induced of mitochondrial membrane depolarization. Naphthofuranquinones induced DNA damage.